Coenzyme q10 and letrozole versus letrozole alone for ovulation induction in polycystic ovary syndrome - Nasrin, Ivy; Ishrat, Shakeela; Amir, Mumtahena; Halder, Suravi; Rahman, Farzana; Kamruzzaman, Mohammad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Polycystic ovary syndrome (PCOS) is the largest single cause of anovulatory infertility. PCOS is associated with oxidative stress. Coenzyme q10 (Coq10) is an antioxidant that protects the mitochondria from damage caused by either insulin resistance or oxidative free radicals. The objective of the study was to compare the effect of combined Coq10 and letrozole than of letrozole alone for ovulation induction in women with PCOS. Methods: This open label parallel design randomized controlled trial study was conducted on 80 infertile women with PCOS selected for ovulation induction. Eligible women were randomized either to combined Coq10 and letrozole (40 patients, 83 cycles) or letrozole alone (38 patients, 91 cycles). The outcome measures were mature follicles, adequate endometrial thickness, ovulation and pregnancy. Results: Mature follicles (≥18-25 mm) were significantly higher in women given Coq10 at 2nd (74.2% vs 31.3%) and 3rd cycles (83.3% vs 28.6%). Adequate endometrial thickness was significantly higher in women given Coq10 in second (90.3% vs 56.3%) and third cycle (94.4% vs 47.6%). When Coq10 was added to letrozole, ovulation rates were significantly higher (87.1% vs 53.1% in second cycle), (83.3% vs 38.1%, in third cycle). Cumulative pregnancy was 2.37 times (95% CI 1.03-5.48) higher in women having Coq10 in addition to letrozole for ovulation induction. Conclusions: Coq10, as an adjuvant to ovulation induction with letrozole improves ovarian response, ovulation and pregnancy in PCOS women. Combination of Coq10 and letrozole can be tried successfully before a more complicated and expensive treatment such as gonadotrophins and laparoscopic ovarian drilling.